Investing at home and abroad: Different costs, different people - Dimitris Christelis; Dimitris Georgarakos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We investigate US households' direct investment in stocks, bonds and liquid accounts and their foreign counterparts, in order to identify the different participation hurdles affecting asset investment domestically and overseas. To this end, we estimate a trivariate probit model with three further selection equations that allows correlations among unobservables of all possible asset choices. Our results point to the existence of a second hurdle that stock owners need to overcome in order to invest in foreign stocks. Among stockholders, we show that economic resources, willingness to assume greater financial risks, shopping around for the best investment opportunities all increase the probability to invest in foreign stocks. Furthermore, we find that households who seek financial advice from relatives, friends and work contacts are less likely to invest in foreign stocks. This result corroborates the conjecture by Hong et al. (2004) that social interactions should discourage investment in foreign stocks, given their limited popularity. On the other hand, we find little evidence for additional pecuniary or informational costs associated with investment in foreign bonds and liquid accounts. Finally, we show that ignoring correlations of unobservables across different asset choices can lead to very misleading results.
urn:nbn:de:hebis:30-73586
Keywords: C35; D14; G11; G35; 330; Foreign Assets; Household Finance; Stockholding; Multivariate Probit; Simulated Maximum Likelihood; Selection; Kapitalanlage; Portfolio-Investition; Privater Haushalt; Anlageverhalten; Schätzung; USA